ANALISIS STUDI KELAYAKAN PENGEMBANGAN USAHA CANOPY DAN ATAP BAJA RINGAN PADA CV. BAJA JAYA LAS MUARA BULIAN - Muryati Muryati; Feny Juhanti (Universitas Batanghari Jambi, 2018)
The objective of this study was to determine how much investment is needed for development of Canopy and Light Steel Roof business in Lembah Kuamang village, Pelepat Ilir sub-district, Muara Bungo District. And then, was to assess all the aspect in business development of Canopy and Light Steel Roof and to assess the business development feasibility by analyzing Investment Criteria. The investment needed was Rp. 564,210,000,- which consists their own capital was Rp. 394,210,000,- bank loan was Rp. 170,000,000,- through bank credit at BRI Bank with 9% interest rate. Aspects were assess, include legal aspects, management aspects and Human Resources, market and marketing aspects, technical and technological aspects, financial and economic aspects. From the evaluation of business development feasibility of Canopy and Light Steel Roof in Lembah Kuamang village, Pelepat Ilir sub-district, Muara Bungo District, this business was feasible to be developed. Based on calculations using the investment criteria analysis on CV. Baja Jaya Las in Lembah Kuamang village, the result was: NPV: Rp. 223,944,943,452,- was greater than 1 means that this business is feasible to be developed, IRR 27.07% was greater than SOCC means that this business is feasible to be developed, NET B/C 1.56 was greater than 1 means this business is feasible to be developed, GROSS B/C 1.04 was greater than 1 means that this business is feasible to be developed, PR 2.08 was greater than 1 means that this business is feasible to be developed, BEP for 3 Years 9 Months 20 Days was greater than the economic age means that this business is feasible to be developed.